Conservation of the Ustilago maydis effector See1 in related smuts - Redkar, Amey (Plant Signal Behav, 2015)
Ustilago maydis is a biotrophic fungus that induces formation of tumors in maize (Zea mays L). In a recent study we identified See1 (Seedling efficient effector 1) as an U. maydis organ-specific effector required for tumor formation in leaves. See1 is required for U. maydis induced reactivation of plant DNA synthesis during leaf tumor progression. The protein is secreted from biotrophic hyphae and localizes to the cytoplasm and nucleus of plant cell. See1 interacts with maize SGT1, a cell cycle and immune regulator, interfering with its MAPK-triggered phosphorylation. Here, we present new data on the conservation of See1 in other closely related smuts and experimental data on the functionality of See1 ortholog in Ustilago hordei, the causal agent of barley covered smut disease.